Maternal and Perinatal Outcome in Women with COVID-19: a Hospital based Descriptive study - Maskey, Suvana; Rijal , Hima (Journal of Institute of Medicine Nepal, 2023)
Introduction Since the declaration of the pandemic by World Health Organization (WHO), COVID-19 infection has affected worldwide including vulnerable pregnant women, who are at risk of increased maternal as well as neonatal morbidities and mortality. This study aimed to evaluate the prevalence of COVID-19 as well as maternal and perinatal outcomes in pregnancy with covid infection compared to pregnancy without infection. Methods This hospital-based descriptive study was conducted in Tribhuvan University Teaching Hospital Obstetrics Department. All pregnant women delivered after the third trimester, positive for COVID-19 during the study period, were compared with age-matched control without infection for maternal outcomes in terms of morbidities, mode of delivery, complications as well as neonatal outcomes such as birth weight, Apgar score, intrauterine fetal demise (IUFD), Neonatal Unit (NNU), Neonatal intensive care unit (NICU) admission and neonatal death. Data were analyzed using Stata 14.1. Results During the study period, total 59 women with covid infection (prevalence 2.23%) and 118 women without infection were included. Obstetric complications were seen significantly more in study group than control group (13.55% vs 3.38%; p value 0.01). Cesarean section and intensive care unit admission were also significantly more in study group than control group (81.35% vs 51.7%; p value <0.001, 22.03% vs 0.85%, p value <0.001). Women with COVID-19 infection had significantly more hospital stay than control group (p value 0.005). but no significant difference was observed in the neonatal outcome. Conclusion Pregnancy with COVID-19 infection is associated with adverse obstetric complications, lower uterine segment Cesarean section and NICU admission but not with adverse neonatal outcomes compared to women without COVID-19 infection.